Online Learning in Covid-19 Pandemic: New Student Perspective at Islamic Religious Education Program - Suwarno .; Edy Saputra; Kharisul Wathoni; Muhammad Tamrin; Amalia Nur Aini (AL-ISHLAH: Jurnal Pendidikan, 2021)
New students for the 2020/2021 academic year have never experienced a direct meeting with the campus since registering, undergoing the orientation period, and lectures are all done online. This study aims to determine the opinion of new students of the Islamic Religious Education study program towards the lectures they undergo. This research uses mixed methods research, which is a combination of qualitative and quantitative research. The research was conducted at IAIN Takengon Central Aceh, IAIN Ponorogo East Java, University of Muhammadiyah Kupang, and IAIN Samarinda. The data collection technique used an open questionnaire distributed via a google form. Analysis of the data used is qualitative and quantitative analysis. Qualitative analysis is used to analyze the reasons for students in online lectures. In contrast, quantitative analysis is used to analyze students' opinions who are happy or not with online lectures by percentage. The results showed that at IAIN Takengon 24.6% of students who liked to study online were happy. In comparison, 75.4% of those who were not happy, at IAIN Ponorogo who liked to study online were 35.8% and 64.2% who were not happy, at the University Muhammadiyah Kupang who like online lectures are 40%. Those who are not happy are 60%, and at IAIN Samarinda who like online lectures are 19.8% who are not happy at 80.2%. Overall, new students who enjoy studying online are 30.05%, and those who are not happy are 69.95%.